Safety Model for the Introduction of Robotic Surgery in Gynecology - Mariano Tamura Vieira Gomes; Beatriz Taliberti da Costa Porto; Jose Pedro Parise Filho; Ana Luiz Vasconcelos; Bruna Fernanda Bottura; Renato Moretti Marques (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To analyze the perioperative results and safety of performing gynecological surgeries using robot-assisted laparoscopy during implementation of the technique in a community hospital over a 6-year period. Methods This was a retrospective observational study in which the medical records of 274 patients who underwent robotic surgery from September 2008 to December 2014 were analyzed. We evaluated age, body mass index (BMI), diagnosis, procedures performed, American Society of Anesthesiologists (ASA) classification, the presence of a proctor (experienced surgeon with at least 20 robotic cases), operative time, transfusion rate, perioperative complications, conversion rate, length of stay, referral to the intensive care unit (ICU), and mortality. We compared transfusion rate, perioperative complications and conversion rate between procedures performed by experienced and beginner robotic surgeons assisted by an experienced proctor. Results During the observed period, 3 experienced robotic surgeons performed 187 surgeries,while 87 surgeries were performedby 20 less experienced teams, always with the assistance of a proctor. The median patient age was 38 years, and the median BMI was 23.3 kg/m2. The most frequent diagnosis was endometriosis (57%) and the great majority of the patients were classified as ASA I or ASA II (99.6%). The median operative time was 225 minutes, and the median length of stay was 2 days. We observed a 5.8% transfusion rate, 0.8% rate of perioperative complications, 1.1% conversion rate to laparoscopy or laparotomy, no patients referred to ICU, and no deaths. There were no differences in transfusion, complications and conversion rates between experienced robotic surgeons and beginner robotic surgeons assisted by an experienced proctor. Conclusion In our casuistic, robot-assisted laparoscopy demonstrated to be a safe technique for gynecological surgeries, and the presence of an experienced proctor was considered a highlight in the safety model adopted for the introduction of the robotic gynecological surgery in a high-volume hospital and, mainly, for its extension among several surgical teams, assuring patient safety.